Kebijakan Perubahan Iklim Di Papua: Kolaborasi Antara Pemerintah Dan Masyarakat Adat - Wijaya, Nasri; Rahail, Emiliana B.; Jaya, Andi Ervin Novara (Universitas Musamus, 2025)
Papua, with Indonesia's richest biodiversity, faces significant climate change challenges. Sustainable policies require synergy among stakeholders, including indigenous communities with their local knowledge and traditional practices. The forest, seen as